Penggunaan Konsep Lean untuk Meningkatkan Efisiensi Pelayanan Instalasi Farmasi Rawat Jalan di Rumah Sakit Anna Medika Bekasi - Zahra, Dima Lintya Siti Karima (UI Scholars Hub, 2015)
The National Health Insurance which was launched on January 1, 2014, is a form of transformation and reformation of health services in Indonesia. In implementation of the JKN, Hospital Pharmacy Installation is forced to improve its quality service sustainably in order to achieve cost effective and efficient service. Lean is a management system that fully focuses on effiency with the objectives to reduce stock, service cycle time and cost. Research was conducted on outpatient pharmacy installation service at Anna Medika Bekasi Hospital in April to May 2016. It focuses on prescription process flow of non-pulvis medicine using action research method with qualitative and quantitative approach. Lean concepts has been applied in this research. The result shows that the cycle time required for processing prescription of non-pulvis medicine is longer than the takt time. It indicates that outpatient pharmacy installation service is unable to fullfil the patient demand, there is lack of human resources on day shift, additional resources are required to support the service and process flow of non-pulvis medicine needs to be redesigned. This new design could result to increment 22.73% of value added activities from 35,89% to 58,62% To ensure the new process flow runs consistently and sustainably, some improvements, which are divided into short, medium and long term, are suggested.